Exploring the influence of food labels and advertisements on eating habits of children: a cross-sectional study from Punjab, India - Madhur Verma; Ramnika Aggarwal; Bhola Nath; Rakesh Kakkar (BMC, 2023)
Abstract Background Maintaining healthy eating habits among children is challenging due to industrial tactics. There is little research on the effect of nutritional labels and tv ads on the eating habits of children. So the primary aim of the study was to explore the noticeability of the food packaging labels by the children, the information retrieved from the food nutrition labels, and their role in increased frequency of eating out in addition to the perceptions of their parents about the television ads. Methods A cross-sectional study was conducted at schools in Punjab, India. Using multi-stage stratified random sampling, we included 722 school-going children aged 14-18 and their parents. A structured predefined questionnaire collected data using a four-point Likert scale. Descriptive statistics and binary logistic regression were used to draw our inferences. Results About 46% of children were eating out > 3 times a week. Nearly 49% said they never looked at the expiry dates on the food packet, and 40% have yet to notice the quality certification. Nearly half do not understand the components of the food label, and 59% said they never changed their buying behavior because of the label. Only 37% of parents expressed their concerns about the timing of the ads when children watch television, while only 25.5% were concerned about the accuracy of the information. Concerns of the parents regarding the timing of the ads, and celebrity endorsements, were potential predictors for the increased frequency of eating out by the children. Conclusions Low awareness regarding the utility of nutrition labels and minimal concerns of the parents increase the frequency of eating out. Unification of our existing policies regarding food labels and tv advertisements to develop family-centric interventions will bring us one step closer to improving the enabling environment to curb the growing menace of childhood obesity.